2015
DOI: 10.1186/s40813-015-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of porcine epidemic diarrhea virus survival in individual feed ingredients in the presence or absence of a liquid antimicrobial

Abstract: BackgroundContaminated complete feed and porcine plasma are risk factors for PEDV introduction to farms and a liquid antimicrobial has been proven useful for reducing risk. This study provides information on the survivability of PEDV across common swine feed ingredients in the presence or absence of the liquid antimicrobial.ResultsEighteen ingredients commonly included in commercial swine diets were selected, including 3 grain sources (corn, soybean meal (SBM), dried distillers grains with solubles (DDGS)), 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
85
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 11 publications
9
85
0
4
Order By: Relevance
“…This indicates that some ingredients had an immediate effect on virus survival that caused a decrease before the incubation period even started. This immediate variation in virus survival was also observed in another experiment measuring on the survival of PEDV in various feed ingredients, with CT values ranging from 16 to 36 on the first day of incubation despite being inoculated with the same virus inoculum of a CT value of 16.3 [23]. This immediate variation in virus concentration could also indicate differences in percent recovery of virus using our modified elution method between the different viruses and feed ingredients.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This indicates that some ingredients had an immediate effect on virus survival that caused a decrease before the incubation period even started. This immediate variation in virus survival was also observed in another experiment measuring on the survival of PEDV in various feed ingredients, with CT values ranging from 16 to 36 on the first day of incubation despite being inoculated with the same virus inoculum of a CT value of 16.3 [23]. This immediate variation in virus concentration could also indicate differences in percent recovery of virus using our modified elution method between the different viruses and feed ingredients.…”
Section: Discussionsupporting
confidence: 71%
“…These previous experiments compared the virus survival at stored external temperatures [23]. No studies have been conducted to evaluate PDCoV and TGEV survival among various types of feed ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to low success rate of PDCoV VI in cell culture, currently PDCoV VI is not a reliable assay to determine whether infectious virus is present in a clinical specimen or if 'X' treatment will inactivate the virus. For PEDV, swine bioassay has been commonly used to assess infectivity of PEDV present in various samples, including feed and feed ingredients after disinfectant or other treatments (Bowman et al, 2015b;Dee et al, 2014b;Dee et al, 2015). Notably, some samples were PEDV VI negative after treatment but swine bioassay positive (Dee et al, 2015), emphasizing the importance and necessity of performing swine bioassay to reliably determine virus infectivity of a sample.…”
Section: Swine Bioassaymentioning
confidence: 99%
“…
Recent research has confirmed that porcine epidemic diarrhea virus (PEDV) can be transmitted by swine feed and ingredients (Dee et al, 2014(Dee et al, , 2015Schumacher et al, 2015). In a review by Nitikanchana (2014) ABSTRACT: Porcine epidemic diarrhea virus (PEDV) is a heat-sensitive virus that has devastated the U.S. swine industry.
…”
mentioning
confidence: 99%